2008
DOI: 10.1128/jcm.00797-08
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of DNA in Plasma by an Automated Real-Time PCR Assay (Cytomegalovirus PCR Kit) for Surveillance of Active Cytomegalovirus Infection and Guidance of Preemptive Therapy for Allogeneic Hematopoietic Stem Cell Transplant Recipients

Abstract: The performance of a plasma real-time PCR (cytomegalovirus [CMV] PCR kit; Abbott Diagnostics) was compared with that of the antigenemia assay for the surveillance of active CMV infection in 42 allogeneic hematopoietic stem cell transplantation (Allo-SCT) recipients. A total of 1,156 samples were analyzed by the two assays. Concordance between the two assays was 82.2%. Plasma DNA levels correlated with the number of pp65-positive cells, particularly prior to the initiation of preemptive therapy. Fifty-seven epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
94
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 44 publications
3
94
1
3
Order By: Relevance
“…Our finding was not unexpected, as we have previously shown that an AG level of 1 positive cell/200 000 PMNLs corresponded roughly to 250 CMV DNA copies/mL. 6 The above discrepancies are likely to be related to the different study design, as well as to differences in the clinical characteristics of patients, the sensitivity of the QRT-PCR employed for CMV surveillance and the CMV DNA load threshold established for initiation of antiviral therapy.…”
mentioning
confidence: 42%
See 2 more Smart Citations
“…Our finding was not unexpected, as we have previously shown that an AG level of 1 positive cell/200 000 PMNLs corresponded roughly to 250 CMV DNA copies/mL. 6 The above discrepancies are likely to be related to the different study design, as well as to differences in the clinical characteristics of patients, the sensitivity of the QRT-PCR employed for CMV surveillance and the CMV DNA load threshold established for initiation of antiviral therapy.…”
mentioning
confidence: 42%
“…Until April 2010 (group I; n ¼ 90), CMV surveillance was performed in parallel by the AG assay and by a plasma real-time PCR assay (Abbott CMV PCR Kit, Abbott Diagnostics, Des Plaines, IL, USA). 6 In this group, pre-emptive therapy was initiated upon a positive AG assay (X1 positive cell/200 000 polymorphonuclear leukocytes) and stopped upon two consecutive negative results after a minimum of 2 weeks of treatment, as previously described. 6 Since May 2010 (group II; n ¼ 57), virological monitoring was exclusively performed by QRT-PCR, and pre-emptive therapy was initiated upon a plasma CMV DNAemia threshold level of 500 CMV DNA copies/mL and was discontinued after two consecutive PCR-negative (undetectable) results, after a minimum of 2 weeks of treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate productive viral infection, we measured HHV DNA in plasma 16, 17. Although control cord blood samples were negative for the presence of HHVs in our measurements, we set an arbitrary level of 100 copies of viral DNA per microliter of plasma as a threshold for positivity.…”
Section: Resultsmentioning
confidence: 99%
“…Rather than focusing on HHV replication in particular cells, we evaluated DNA of all HHV types in plasma, into which the productively infected cells may release viruses 17. This analysis revealed all HHVs in plasma of healthy controls and patients with SCAD and ACS.…”
Section: Discussionmentioning
confidence: 99%